Sistem Informasi Geografis untuk Pemetaan Puskesmas di Dinas Kesehatan Kabupaten Sumba Barat Daya - Yulius Talo Popo; Cecilia Dai Payon Binti Gabriel; Paulus Mikku Ate (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
GIS is a database system that has special features to process information related to the same space with operating system devices. GIS is also capable of integrating data, organizing information, and analyzing data that can ultimately produce outputs to support decision-making related to geographic issues. In this study, researchers plan to apply GIS to function as a digital map, which can certainly represent a particular area, and can be utilized through the availability of information by Google map as a wayfinding. In this study, it can be concluded that the benefits of GIS for mapping health centers to provide information about the location of health centers to the Health Office of Southwest Sumba Regency.